Gas som bedövningsmetod vid slakt av slaktkyckling - Skavnes, Marie (SLU/Dept. of Animal Environment and Health (until 231231), 2004)
Electrical stunning is the method that has been used in Sweden to stun broilers prior to slaughter. However, for reasons of animal welfare and meat quality, research has been made in the EU to develop new stunning methods. Gas stunning is now regarded as the best alternative. In this study literature has been reviewed with focus on different gas stunning systems and observations have been made at two different slaughterhouses regarding animal welfare before, during and directly after stunning. At one slaughter plant carbondioxide was used in a two-stage system where the birds were standing on a conveyer belt during the stunning procedure. At the other slaughter house a lethal gas mixture containing argon was used and the birds were stunned still sitting in the transport container. The study identified several advantages and disadvantages with both of these stunning systems and recommendations were made to improve animal welfare at the slaughterhouses. One important goal is to reduce the handling of animals prior to stunning in order to avoid injuries and stress to the birds. Routines for controlling consciousness in the birds after stunning and having standards regarding the handling of conscious birds prior to bleeding are fundamental in achieving good animal welfare. Each and every person working with live animals needs to have the ethics of animal welfare in mind at any time.